A Comparison of Commercially Available Screen-Printed Electrodes for Electrogenerated Chemiluminescence Applications - Kerr, Emily; Alexander, Richard; Francis, Paul S.; Guijt, Rosanne M.; Barbante, Gregory J.; Doeven, Egan H. (Frontiers in Chemistry, 2021)
We examined a series of commercially available screen-printed electrodes (SPEs) for their suitability for electrochemical and electrogenerated chemiluminescence (ECL) detection systems. Using cyclic voltammetry with both a homogeneous solution based and a heterogeneous bead based ECL assay format, the most intense ECL signals were observed from unmodified carbon-based SPEs. Three commercially available varieties were tested, with Zensor outperforming DropSens and Kanichi in terms of sensitivity. The incorporation of nanomaterials in the electrode did not significantly enhance the ECL intensity under the conditions used in this evaluation (such as GNPs 19%, CNTs 45%, CNFs 21%, GPH 48% and OMC 21% compared to the ECL intensity of unmodified Zensor carbon electrode). Platinum and gold SPEs exhibited poor relative ECL intensities (16% and 10%) when compared to carbonaceous materials, due to their high rates of surface oxide formation and inefficient oxidation of tri-n-propylamine (TPrA). However, the ECL signal at platinum electrodes can be increased ~3-fold with the addition of a surfactant, which enhanced TPrA oxidation due to the hydrophobicity of the electrode surface. Our results also demonstrate that each SPE should only be used once, as we observed a significant change in ECL intensity over repeated CV scans and SPEs cannot be mechanically polished to refresh the electrode surface.